A Classical Study on Istighāthah and the Boundaries of Shirk in Islamic Creed - Alya Fasya; Annafi'atuz Zahro'; Agung Pranoto Kadiatmaja (Konsultan Jurnal Ilmiah Indonesia, 2025)
This study examines the contribution of classical creedal literature in explaining the concept of istighāthah and defining the boundaries of shirk in Islamic theology, while also assessing its relevance to contemporary istighāthah practices that often spark debate among Muslims. Using a qualitative descriptive approach and library research methods, this study traces the major works of scholars to find the principles of faith used to determine whether a request for help is a valid act of worship or has crossed the boundaries of tawhid into shirk. The results of the study show that there are three main principles that are strongly emphasized by classical scholars: attributing divine attributes to creatures, transferring mahdah worship to other than Allah, and inner beliefs that place creatures as independent owners of supernatural abilities. These three principles have proven to remain relevant in addressing the problems of modern istighāthah, especially in distinguishing between worldly requests for help, tawassul that is still within the corridor of sharia, and supernatural requests that contain elements of shirk. This study emphasizes the importance of examining contemporary religious practices through the framework of classical creed so that the community can understand the difference between reverence, tawassul, and forms of divine attribution that are not permitted in Islam.